Long-term care insurance in Italy: medico-legal and socio-economic profiles - Bailo, Paolo; Pesel, Giuliano; Gibelli, Filippo; Sirignano, Ascanio; Ricci, Giovanna (Frontiers in Public Health, 2024)
Long-term care insurance (LTCI) plays a crucial role in providing substantial aid in non-self-sufficient situations and complementing existing state protection mechanisms. With an aging population and increasing demand for healthcare services LTC policies have become indispensable. While individual LTCI policies face adoption challenges, group insurances offer a more streamlined alternative. However, realizing the full potential of these insurances necessitates targeted legislative intervention to improve accessibility and ensure sustainability. This article explores the evolution of LTCI policies in Italy, offering an overview of the current landscape and highlighting the socio-economic and medico-legal factors shaping the present scenario. By providing this analysis, we seek to offer insights into the dynamic evolution of LTCI policies and the crucial role of legislative measures in enhancing their effectiveness and accessibility.